Hot air treatment mitigates chilling injury in mango fruit by enhancing antioxidant system activity - Chongchatuporn, Ukrit; Wisutiamonkul, Apinya; Ketsa, Saichol (Agriculture and Natural Resources, 2024)
Importance of the work: Mango fruit is sensitive to chilling injury when stored below 12 C. Heat treatment can delay or reduce this chilling injury. Objectives: To investigate the effects of heated air treatment on chilling injury and the antioxidant system in mango stored at 4C. Materials & Methods: Mature mango fruits were treated with heated air at 38C for 3 days, while the control fruits were held at room temperature. After heated air treatment, all fruits were stored at 4°C. Control and stored fruits were assessed for chilling injury and antioxidant system activity in the peel. Results: Mango cv. Nam Dok Mai fruits stored at 4C had significant peel browning (chilling injury) that became more severe after transfer to room temperature. Fruits exposed to heated air heat treatment at 38°C (60% RH) for 3 days before storage at 4°C had delayed peel browning for up to 3.5 days during and after cold storage. Heat treatment increased total antioxidant activity capacity and catalase activity. Heated air treatment did not reduce ascorbate peroxidase, guaiacol peroxidase, and superoxide dismutase activities in the mango peel, both during storage at 4C and after transfer to room temperature (27-28°C, 75% RH). Main finding: Heated air treatment increased chilling injury tolerance in mango and was associated with total antioxidant capacity and catalase activity, but not with the activities of ascorbate peroxidase, guaiacol peroxidase, and superoxide dismutase.